Disturbed soil properties and geotechnical design - Schofield, A. N. 1930-; Haigh, Stuart (ICE Publishing, 2018)
This is an easily accessible account of critical state of soil mechanics, geotechnical centrifuge testing and the original Cam-Clay model invented by the author.
This edition previously issued in print in 2017. Digital resoure published 2018.
Keywords: Soil mechanics.; Geotechnical engineering.; elektronické knihy; electronic books